SPE Improved Oil Recovery Symposium 2012
DOI: 10.2118/154169-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Scale Evaluation of Polymers Displacing Viscous Oil – Computational Fluid Dynamics Simulation of Micromodel Experiments

Abstract: Recovery of viscous oil can be significantly improved by injecting polymer solutions. The processes leading to increased oil production occur on a large scale -improving vertical and areal sweep efficiency -but they begin on a micro scale.Micromodels with realistic pore geometries have been created. These micromodels were saturated with viscous oil and the displacement of the oil by water and polymer solutions investigated experimentally. Polymer injection reduced fingering compared with water injection and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In response to this need, we have now demonstrated that the polymer concentration C p has a significant influence on the dynamics and patterns of interface displacement and phase distribution (even when the flowrate is kept constant) due to the effects of C p on the effective viscosity of the polymer solution. In contrast to previous studies [2,20,[24][25][26][27][28], the dependency of M and S ro on Ca could be analyzed. Using a series of microfluidic experiments, we showed the capability of C p to alter the value and range of Ca and M, which, in turn, determine the stability of the invasion front as well as the mobilization and fragmentation of the resulting ganglia.…”
Section: Ganglia Size Distribution and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In response to this need, we have now demonstrated that the polymer concentration C p has a significant influence on the dynamics and patterns of interface displacement and phase distribution (even when the flowrate is kept constant) due to the effects of C p on the effective viscosity of the polymer solution. In contrast to previous studies [2,20,[24][25][26][27][28], the dependency of M and S ro on Ca could be analyzed. Using a series of microfluidic experiments, we showed the capability of C p to alter the value and range of Ca and M, which, in turn, determine the stability of the invasion front as well as the mobilization and fragmentation of the resulting ganglia.…”
Section: Ganglia Size Distribution and Analysismentioning
confidence: 99%
“…Other authors [28] carried out computational fluid dynamics simulations using a digitalised pore network to investigate the non-Newtonian fluid displacement at the microscale and compared their results with the flooding experiments [20]. In previous work [2], a micromodel study was performed to investigate the effects of rheological properties of several complex fluids used in EOR on oil recovery.…”
Section: Introductionmentioning
confidence: 99%